Cultural Meaning and Values of the Beriuk Tinjal Dance at the Rengganis Art Studio - Balqis, Lale Alia; Malarsih, Malarsih; Sinaga, Syahrul Syah (LPPM Institut Seni Indonesia Padangpanjang, 2024)
The Beriuk Tinjal dance is a traditional performing art from Lombok, West Nusa Tenggara, preserved through the Rengganis Art Studio. This study aims to explore the philosophical meanings and cultural values embedded in the Beriuk Tinjal dance and to assess the strategic role of the art studio in sustaining this heritage amidst globalization. Using a qualitative approach with methods including observation, interviews, and literature review, this research uncovers that the dance embodies the Sasak community's core values, such as unity, harmony, and respect for ancestors. Each dance movement holds symbolic meaning, reflecting the cycles of human life, environmental stewardship, and spiritual devotion. Moreover, the Rengganis Art Studio acts as a guardian of tradition by integrating moral education and cultural identity into its training programs for younger generations. This study highlights the dance's dual role as an aesthetic and educational medium, providing insights into the interplay between art and cultural sustainability. The findings underscore the importance of community-based initiatives in preserving traditional arts while adapting to modern challenges. These results contribute to broader discussions on cultural preservation and the revitalization of intangible heritage in contemporary society